Enhanced post-traumatic headache-like behaviors and diminished contribution of peripheral CGRP in female rats following a mild closed head injury. (June 2020) - Bree, Dara; Mackenzie, Kimberly; Stratton, Jennifer; Levy, Dan
Introduction: Females are thought to have increased risk of developing post-traumatic headache following a traumatic head injury or concussion. However, the processes underlying this susceptibility remain unclear. We previously demonstrated the development of post-traumatic headache-like pain behaviors in a male rat model of mild closed head injury, along with the ability of sumatriptan and an anti-calcitonin-gene-related peptide monoclonal antibody to ameliorate these behaviors. Here, we conducted a follow-up study to explore the development of post-traumatic headache-like behaviors and the effectiveness of these headache therapies in females subjected to the same head trauma protocol. Methods: Adult female Sprague Dawley rats were subjected to a mild closed head injury using a weight-drop device (n = 126), or to a sham procedure (n = 28). Characterization of headache and pain related behaviors included assessment of changes in cutaneous cephalic and extracephalic tactile pain sensitivity, using von Frey monofilaments. Sensitivity to headache/migraine triggers was tested by examining the effect of intraperitoneal administration of a low dose of glyceryl trinitrate (100 µg/kg). Treatments included acute systemic administration of sumatriptan (1 mg/kg) and repeated systemic administration of a mouse anti-calcitonin gene-related peptide monoclonal antibody (30 mg/kg). Serum levels of calcitonin gene-related peptide were measured at baseline and at various time points post head injury in new cohorts of females (n = 38) and males (n = 36). Results: Female rats subjected to a mild closed head injury developed cutaneous mechanical hyperalgesia, which was limited to the cephalic region and was resolved 4 weeks later. Cephalic pain hypersensitivity was ameliorated by treatment with sumatriptan but was resistant to an early and prolonged treatment with the anti-calcitonin gene-related peptide monoclonal antibody. Following the resolution of the head injury-evoked cephalic hypersensitivity, administration of glyceryl trinitrate produced a renewed and pronounced cephalic and extracephalic pain hypersensitivity that was inhibited by sumatriptan, but only partially by the anti-calcitonin gene-related peptide treatment. Calcitonin gene-related peptide serum levels were elevated in females but not in males at 7 days post head injury. Conclusions: Development of post-traumatic headache-like pain behaviors following a mild closed head injury, and responsiveness to treatment in rats is sexually dimorphic. When compared to the data obtained from male rats in the previous study, female rats display a prolonged state of cephalic hyperalgesia, increased responsiveness to a headache trigger, and a poorer effectiveness of an early and prolonged anti-calcitonin gene-related peptide treatment. The increased risk of females to develop post-traumatic headache may be linked to enhanced responsiveness of peripheral and/or central pain pathways and a mechanism independent of peripheral calcitonin gene-related peptide signaling.